Evaluation of worker body posture in the ice block moving process using the Rapid Entire Body Assessment (REBA) method - Azwinur Azwinur; Ziyad Muammar; Usman Usman (Journal of Mechafa Engineering and Fabrication, 2026)
Ergonomics is an important aspect in the industrial work environment, especially in maintaining worker well-being and increasing productivity. One of the main factors in ergonomics is the worker's posture during work activities, which has the potential to cause musculoskeletal disorders (MSDs). CV XYZ, which is engaged in ice block production in Lhokseumawe, has a production capacity of up to 1,200 ice blocks per day with a work process that is still dominated by manual activities. Based on the results of initial observations, complaints of pain were found in the workers' waist and right shoulder, which indicates an ergonomic risk. This study, aXYZ, analyses the relationship between work posture and MSD complaints using the Rapid Entire Body Assessment (REBA) method. The study was conducted descriptively and qualitatively through direct observation, interviews, and literature studies. The REBA assessment was carried out by measuring the body angles at the neck, back, arms, wrists, and legs during work activities. The results showed that for the first worker, the activity of removing ice blocks from the mould received a REBA score of 10 (high risk), while the process of arranging ice into vehicles received a score of 7 (moderate risk). For the second and third workers, each work activity received a score of 7 (moderate risk). These results are supported by Standard Nordic Questionnaire (SNQ) data, which indicated that the dominant complaints were in the shoulders and waist due to repetitive movements and non-ergonomic work postures. It can be concluded that several work activities pose ergonomic risks that require immediate improvement, particularly the process of removing ice cubes from the mould. Improvements can be made through the use of more ergonomic tools and improved work methods to reduce the risk of injury to workers